Development, Implementation, and Outcomes of a Global Infectious Disease Training Course - Miguela A Caniza; Maysam Homsi; Miriam Gonzalez; Daniel C Moreira; Li Tang; Elisabeth Adderson; Carlos Rodriguez-Galindo (Journal of Medical Education and Curricular Development, 2021)
Background: Skilled healthcare professionals are critical for providing quality healthcare for children with cancer globally. Training curricula addressing the knowledge needs in infection care and prevention (ICP) in cancer are scarce. Program description: We implemented a 10-week blended course in ICP. The distance learning had four 2-week modules: Infectious Complications, Quality in Infection Care, Quality in Infection Prevention, and Sustainability, Research, and Dissemination. Each module had pre- and post-tests and weekly webinars. The 2-week in-person learning had lectures, group exercises, clinical observations, hospital and laboratory tours, and ended in an annual conference. An individual project developed during the distance learning was presented in the in-person workshop. Course attendance criteria were English language proficiency and participants’ role in ICP at their institutions. Program evaluation and results: Twenty-two students from 17 hospitals in 10 countries completed the course, developed a project, and answered surveys covering knowledge assessments and satisfaction, and 6-month course and 1-year project follow-ups. Pretest and post-test scores revealed knowledge improvement ( P  < .001). Participants rated the distance learning as outstanding (63%) or good (28%); and the in-person as outstanding (87%). In the follow-up survey, graduates felt more comfortable at managing infections and participated more in quality improvement and academics at their institutions. Seventeen participants (77%) took steps to implement their study projects, and 9 were successful. Collaboration and networking of trainees were notable outcomes. Discussion: The ICP course is a resource to improve knowledge, engage graduates in network collaborations, and a reliable model to develop other thematic healthcare global training programs.